Bacterial Community Diversity Associated With Different Utilization Efficiencies of Nitrogen in the Gastrointestinal Tract of Goats - Wang, Lizhi; Liu, Kaizhen; Wang, Zhisheng; Bai, Xue; Peng, Quanhui; Jin, Lei (Frontiers in Microbiology, 2019)
The objective of this study was to examine the association between bacterial community structure and the utilization efficiency of nitrogen (UEN) phenotypes by determining the bacterial community in the gastrointestinal tract (GIT) of goats that differ in UEN using high-throughput 16S rRNA gene sequencing. Thirty Nubian goats were selected as experimental animals, and their UEN was determined in a metabolic experiment. Subsequently, eight individuals were grouped into the high nitrogen utilization (HNU) phenotype, and seven were grouped into the low nitrogen utilization (LNU) phenotype. The bacterial 16S rRNA gene amplicons from the rumen, abomasum, jejunum, cecum and colon contents of these animals were sequenced using next-generation high-throughput sequencing technology. Two hundred thirty-nine genera belonging to 23 phyla in the rumen, 319 genera belonging to 30 phyla in the abomasum, 248 genera belonging to 36 phyla in the jejunum, 248 genera belonging to 25 phyla in the colon and 246 genera belonging to 23 phyla in the cecum were detected, with Bacteroidetes and Firmicutes predominating. In addition, a significant correlation was observed between the UEN and the genera Succiniclasticum, Bacteroides, Ruminobacter, Methanimicrococcus, Mogibacterium, Eubacterium_hallii_group and Ruminococcus_1 in the rumen; Bacteroidales_S24-7_group, Bacteroidales_RF16_group, Bacteroidales_UCG-001 and Anaerovibrio in the abomasum; Ruminococcus_2, Candidatus_Saccharimonas, Candidatus_Arthromitus and Coprococcus_1 in the jejunum; Erysipelotrichaceae_UCG-004, Akkermansia, Senegalimassilia, Candidatus_Soleaferrea and Methanocorpusculum in the colon; and Ruminococcaceae_UCG-002, Anaerovibrio and Ruminococcaceae_UCG-007 in the cecum. Furthermore, the real-time PCR results showed that the ruminal copies of Fibrobacter_succinogenes, Butyrivibrio_fibrisolvens, Ruminococcus_sp._HUN007, Prevotella ruminicola and Streptococcus bovis in the HNU animals were significantly higher than those in the LNU animals. This study suggests an association of GIT microbial communities as a factor that influences UEN in goats.